Clinical Outcome of Rheumatic Mitral Valve Repair and Replacement Surgery in Indonesia; A Comparison with Non-Rheumatic Aetiology - Amiliana Mardiani Soesanto; Estu Rudiktyo; Amin Tjubandi; Rina Ariani; Fadhila Nafilah Azzahra; Mochammad Faisal Adam; Ario Soeryo Kuncoro (Ubiquity Press, 2024)
Introduction: Mitral valve repair (MVr) has been shown to achieve better outcomes than mitral valve replacement (MVR) in degenerative aetiology. However, that cannot be applied in rheumatic mitral valve disease. Therefore, this study aims to evaluate early and late clinical outcomes and mid-term survival in RHD compared to the non-RHD group and whether mitral valve repair is a better surgical approach in RHD patients. Methods: Patients who underwent mitral valve surgery with or without coronary artery bypass grafting were included in this study. All patients were divided into the RHD and non-RHD group by the type of mitral surgery performed. Early and late outcomes were evaluated, and mid-term cumulative survival was reported. Results: A total of 1382 patients post MV surgeries were included. The 30-day mortality was significantly higher in the RHD group compared to the non-RHD group (8.7% vs. 4.4%, p = 0.003). There was no difference in 30-day mortality between repair and replacement in each respective group. During follow-up (12-54 months), all-cause mortality between RHD and non-RHD groups (16.7% vs. 16.2%) was not different. In the RHD group, the survival of MVr was 85.6% (95% CI 82.0%-88.5%), and MVR was 78.3% (95% CI 75.8%-80.6%), p-value log rank 0.26 However, in the non-RHD group, patients who underwent MVr had better survival than MVR, with cumulative survival of 81.7% (95% CI 72.3%-88.2%) vs. 71.1% (95% CI 56.3%-81.7%) p-value log rank 0.007. Conclusion: Early mortality rate in rheumatic mitral valve surgery was higher than in non-rheumatic valve surgery. Although in rheumatic MV disease MV repair did not show a significant survival advantage over MV replacement, a trend towards more favourable survival in the repair group was observed.